The Semantic Field of Dire Verbs in French - Rifqi Ayu Everina; Myrna Laksman-Huntley (Universitas Pendidikan Indonesia, 2022)
Verbs dire have a wide range of semantic features. Therefore, there are various verbs that are semantically related to this verb. This results in the probability of using verbs that are not correct to describe a concept, idea, or feeling, hence it will cause ambiguity and error. On the contrary, this study discusses the similarities and differences in semantic features contained in dire verbs with an analysis using Leech's (2004) and Nida's (2015) theory of semantic feature. Verbs with dire meaning are research data obtained from the online dictionary Larousse.fr and analyzed using qualitative methods with literature study. There were 49 verbs with dire meaning which were then grouped according to the same components. It was found that the verbs can be classified as telling, dialogue, reading, ordering, articulating, publishing, informing, responding to words or actions, expressing, and affirming. Sketch engine has helped to find the minimum component and shows the verb usage in context. The difference in the use lies in the several components it contains: how to do audible activities, for example articulating, having dialogue, informing; the urgency of dire action, for instance what is contained in ordering and responding to an action or words, verb objects like fairy tales, imaginary stories, or facts; the contents of the discussion, such as facts, secrets, ideas, and thoughts; the way of expressing that is specific, detailed, and precise.